Large-scale distributed systems and energy efficiency : a holistic view - Pierson, Jean-Marc. (Hoboken, NJ : Wiley, 2015)
"This book discusses energy efficiency in large-scale systems. It provides an overview of current energy-reducing technologies and the energy consumption method, addressing topics such as cloud computing, high-performance computing, networks and more. The book begins with an introduction to energy demands in ICT. It then covers topics like green wired/wireless networks, mobile computing, power modeling, green data centers and high-performance computing, resource allocation and energy efficiency in P2P systems"--
4.4.2 Energy Efficiency and QoE in Wireless Mesh Networks4.4.3 Reducing Energy Consumption of the End User Device; 4.4.4 Energy Measurements Revealing Video QoE Issues; 4.4.5 Energy Issues in Environmental WMNs; 4.4.6 Summary; 4.5 Energy-Efficient Medium Access in Wireless Sensor Networks; 4.5.1 MaxMAC -- An Energy-Efficient MAC Protocol; 4.5.2 Real-World Testbed Experiments with MaxMAC; 4.5.3 Summary; 4.6 Energy-Efficient Connectivity in Ad-Hoc and Opportunistic Networks; 4.6.1 Ad-Hoc Networking; 4.6.2 Opportunistic and Delay-Tolerant Networking; 4.6.3 Summary; 4.7 Summary and Conclusions.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Data processing service centers -- Energy conservation; Electronic data processing -- Distributed processing -- Energy conservation; Computer networks -- Energy conservation; Computer networks -- Energy conservation; Data processing service centers -- Energy conservation; Electronic data processing -- Distributed processing -- Energy conservation; COMPUTERS -- Programming -- Parallel; Electronic books; Electronic books